Characteristics of Lung Microbiota in Children's Refractory Mycoplasma pneumoniae Pneumonia Coinfected with Human Adenovirus B. (17th January 2022) - Zhou, Wenxiang; Chen, Jinglong; Xi, Zhimin; Shi, Yanyan; Wang, Libo; Lu, Aizhen
Abstract : Background . Both M. pneumoniae and human adenovirus (HAdV) are common causative agents of lower respiratory tract infection in children; nonetheless, the lung microbiota in patients with coinfection of HAdV and M. pneumoniae remain unexplored. Methods . Thirty-two children, diagnosed with refractory M. pneumoniae pneumonia (RMPP), entered into the one-year study from July 1, 2019 to June 30, 2020. Among them, twenty-one entered into the M. pneumoniae monoinfection (MP) group and eleven entered into the M. pneumoniae and HAdV coinfection (MP&ADV) group. The characteristics of the clinical findings were examined, and the lung microbiota was analyzed by metagenomic next generation sequencing (mNGS). Results . Eleven patients in the MP&ADV group were coinfected with human mastadenovirus species B . The fever days lasted for significantly longer periods in the MP&ADV group than in the MP group (P < 0.05 ). The percentage of CD16 + CD56 + cells was significantly higher in the MP&ADV group than that in the MP group (P < 0.05 ). There were no significant differences in α -diversity between the MP and MP&ADV groups, but the β -diversity was clearly higher in the MP&ADV group than that in the MP group (P < 0.05 ). At the microbial level, the top phylum of the MP BALF microbiota was Tenericutes ; in contrast, it was Preplasmiviricota in the MP&ADV BALF. There were significant differences in the relative abundance of Tenericutes and Preplasmiviricota between the two groups (P < 0.001 ). There was a strong positive correlation between human mastadenovirus B and fever days, M. pneumoniae and level of IgA, and a strong negative correlation between Mycoplasma pneumoniae and PCT. Conclusions . In RMPP, the BALF microbiota in children with mono M. pneumoniae infection was simpler than those with coinfection with human mastadenovirus B . Prolonged fever days were associated with human mastadenovirus B coinfection.